2016
DOI: 10.5194/bg-13-3475-2016
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of previous year's leaf N and soil N uptake to current year's leaf growth in sessile oak

Abstract: Abstract. The origin of N which contributes to the synthesis of N reserves of in situ forest trees in autumn and to the growth of new organs the following spring is currently poorly documented. To characterize the metabolism of various possible N sources (plant N and soil N), six distinct 20-yearold sessile oaks were 15 N labelled by spraying 15 NH 15 4 NO 3 : (i) on leaves in May, to label the N pool remobilized in the autumn for synthesis of reserves, (ii) on soil in the autumn, to label the N pool taken up … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…One explanation for this observation might be a greater soil N depletion by Molinia, leading to a higher demand for internal N remobilization in oak to sustain budburst and leaf development (Neilsen et al 2000;Bausenwein et al 2001). It has been shown that the level of N availability during bud break in oak is a critical factor affecting leaf C capture (Bazot et al 2016;Vernay et al 2016Vernay et al , 2018. Thus the magnitude of internal N recycling from roots might not depend only on limited soil inorganic N amounts but also on neighbour presence and neighbour identity (Welker et al 1991;Kaitaniemi et al 2018).…”
Section: N Allocation Pattern In Oak Was Affected By the Presence Of mentioning
confidence: 99%
“…One explanation for this observation might be a greater soil N depletion by Molinia, leading to a higher demand for internal N remobilization in oak to sustain budburst and leaf development (Neilsen et al 2000;Bausenwein et al 2001). It has been shown that the level of N availability during bud break in oak is a critical factor affecting leaf C capture (Bazot et al 2016;Vernay et al 2016Vernay et al , 2018. Thus the magnitude of internal N recycling from roots might not depend only on limited soil inorganic N amounts but also on neighbour presence and neighbour identity (Welker et al 1991;Kaitaniemi et al 2018).…”
Section: N Allocation Pattern In Oak Was Affected By the Presence Of mentioning
confidence: 99%
“…The reason for this result may be that vegetation needs its own stored carbohydrates and nutrients with one another growth and development, and that delay in vegetation EOS may cause a longer storage period in which to store more reserves [44,45]. These reserves can then be supplied to power shoot development and growth of vegetation in the second year, thus promoting the advance of vegetation SOS [46]. Of course, these explanations are only from the perspective of nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The decreasing total N concentrations of young shoots from the first to the latest harvest, in contrast with the increasing N dff% at both sites reflected weakening support of N reserves, which progressively depleted (Table 3). The difference of shoot N dff% between application dates became smaller (Figure 5 and Table 3), likely suggesting the increasing ability of concurrent uptake in the late spring, and contribution to new spring growth with rising temperature [7,44]. The difference of young shoot N dff% among fertilization dates was closely associated with the GDD values between dates of fertilization and the first harvest (Figures 2 and 6).…”
Section: Thermo Condition and 15 N Utilization In The Following Young...mentioning
confidence: 91%
“…The internal cycling of N reserves contributes a major proportion of N (up to 100%) to support the spring growth of trees, especially when the mineral N availability is low because of the slow mineralization rate under low temperature [6]. In deciduous trees, N reserves are built up by the re-translocation of nutrients in senescing leaves back to branches and roots and/or by absorption in autumn [7][8][9]. In evergreen trees, the N reserves are contributed from the previous absorption during active vegetative growth or the absorption from the soil during vegetative dormancy [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%